Climate Change: What Can Doctors Do? - Thomas Micklewright (European Medical Journal, 2017)
Global warming remains one of the largest global threats to our health. The size of the challenge is immense but political interventions have so far failed to create the drastic changes that are needed to avert this crisis. Concerned by the health risks of climate change, new health groups are emerging to champion this cause, raising awareness, accumulating research data, and influencing public policy. However, there has been less discussion about the role of individual clinicians, particularly family doctors, in addressing this challenge. This article proposes six simple steps that doctors can take to help influence the ‘green’ behaviour of patients, colleagues, and health systems.